Institusi Realisasi Madrasah Aman Bencana: Penerapan Multidisiplin Di Ma Darul Huda Sumbermanjing Wetan - Saida Munawwaroh; Bisyarotul Masfufah; Intan Karisma; Nadia Nabila (KAMPUS AKADEMIK PUBLISING, 2026)
MA Darul Huda Sumbermanjing Wetan, Malang Regency, is located in an area prone to earthquakes and tsunamis, necessitating a comprehensive preparedness model because Indonesia is a region with a high level of geological disaster vulnerability, particularly in the southern coastal areas of Java. The aim of this research is to evaluate efforts to establish a Disaster Safe Madrasah (MAB) using a multidisciplinary approach that combines elements of religion, psychology, and science. The research employs a qualitative approach, involving data collection techniques such as in-depth interviews, field observations, and documentation. Data analysis is conducted interactively through the stages of data reduction, presentation, conclusion drawing, and verification, which ensures that the data is valid through triangulation of techniques and sources. The research results indicate that disaster curriculum, evacuation routes, early warning systems, and regular simulations are ways to realize the implementation of the science pillar. The religious pillar helps instill a theological foundation that mitigation is a form of action and social worship. This allows for the elimination of a fatalistic view of disasters. The psychological pillar, on the other hand, focuses on enhancing mental readiness, panic management, and psychosocial support to help community members become stronger. The synergy of these three pillars demonstrates the ability to form a broad mitigation ecosystem, characterized by increased environmental awareness, discipline, cooperation skills, and a reduced likelihood of mass panic among students. This study found that the pesantren-based MAB model at MA Darul Huda builds the mental and spiritual resilience of the madrasah community while also strengthening its structural aspects. This model can serve as an alternative reference for other madrasahs, especially in disaster-prone areas.